Nélida Piñon no campo literário brasileiro em 1969 - M. Carmen Villarino Pardo (Estudos de Literatura Brasileira Contemporânea)
This paper analyzes the position occupied by Nélida Piñon in the Brazilian literary field in1969, by the time she published her first awarded book, Fundador.